Biopsy series of acute kidney injury from a tertiary care referral center in south India - Sujatha Siddappa; Ramprasad Kowalya (Society of Diabetic Nephropathy Prevention, 2015)
Acute kidney injury (AKI) is common in hospital patients and more so in critically ill patients. It is frequent, harmful and potentially treatable condition. In a total of 243 renal biopsies 130 cases fulfilled the criteria of acute kidney injury. The usual mode of presentation was renal failure followed by acute nephritis. Histopathologically acute interstitial nephritis was the usual finding followed by post infectious-glomerular nephritis. The acute renal failure (ARF) prognosis is influenced by the co-morbidity states and we had a high mortality of 8.46% in our referral centre.